Pharmacological Modulation of Heat Shock Proteins for Enhancing Thermotolerance and Immune Resilience in Heat-Stressed Livestock - Ullah, Shakeeb; Ali, Mubarik; Ashraf, Uzma; Ramzan, Faiqah; Jabeen, Norina; Qamar Ullah,; Hussain, Irtaza (Indus Journal of Bioscience Research, 2024)
Background: Heat stress reduces immunological resilience and cattle output, hence efforts to improve thermotolerance are needed. This study thus aimed to increase thermotolerance and immunological function in heat-stressed cows by pharmacological regulation of HSP70 with resveratrol, quercetin, and geranylgeranyl acetone (GGA). Methods: One hundred and twenty cows aged 2–5 years were involved in this cross-sectional study carried out at Gomal University, Dera Ismail Khan between February 2024 and October 2024. Four groups comprised cows: control, resveratrol (200 mg/day), quercetin (300 mg/day), and GGA (100 mg/day). Treatments were given for sixty days then under thirty-day observation. Rectal temperature, HSP70 expression, antioxidant enzyme activities, and inflammatory markers (IL-6, TNF-α) among physiological, biochemical, and immunological parameters were examined. Results: Treated groups showed notable lower rectal temperature than the control (p < 0.05). Day 60 saw quercetin and GGA reach the lowest temperatures—38.4 ± 0.2°C and 38.5 ± 0.2°C—against the control, 39.0 ± 0.3°C. By day 60, HSP70 concentrations rose dramatically and peaked in the GGA group (p = 0.001) at 3.2 ± 0.3 ng/mL. With SOD (11.5 ± 0.6 U/mg) and catalase (15.3 ± 0.7 U/mg), the GGA group had the highest antioxidant activity (p < 0.05). With the GGA group displaying 9.3 ± 0.7 pg/mL and 16.8 ± 0.8 pg/mL respectively, IL-6 and TNF-α levels likewise dropped (p < 0.05). Conclusion: Heat-stressed cows' thermotolerance, antioxidant defenses and immunological control are improved by pharmacological manipulation of HSP70 with quercetin and GGA. These agents deserve more long-term research since they showed good ways to reduce heat stress in animals.